Timing of phase‐amplitude coupling is essential for neuronal and functional maturation of audiovisual integration in adolescents. Issue 6 (27th April 2020) - Ohki, Takefumi; Matsuda, Takeru; Gunji, Atsuko; Takei, Yuichi; Sakuma, Ryusuke; Kaneko, Yuu; Inagaki, Masumi; Hanakawa, Takashi; Ueda, Kazuhiro; Fukuda, Masato; Hiraki, Kazuo
Abstract: Objective: The ability to integrate audiovisual information matures late in adolescents, but its neuronal mechanism is still unknown. Recent studies showed that phase‐amplitude coupling (PAC) of neuronal oscillations, which is defined as the modulation of high‐frequency amplitude by low‐frequency phase, is associated with audiovisual integration in adults. Thus, we investigated how PAC develops in adolescents and whether it is related to the functional maturation of audiovisual integration. In particular, we focused on the timing of PAC (or the coupling phase), which is defined as the low‐frequency phase with maximum high‐frequency amplitude. Methods: Using magnetoencephalography (MEG) on 15 adults and 14 adolescents while they performed an audiovisual speech integration task, we examined PAC in association cortexes with a trial‐by‐trial analysis. Results: Whereas delta‐beta coupling was consistently observed in both adults and adolescents, we found that the timing of delta‐beta PAC was delayed by 20–40 milliseconds in adolescents compared with adults. In addition, a logistic regression analysis revealed that the task performance improves as the timing of delta‐beta PAC in the right temporal pole (TP) got closer to the trough position (180 degrees). Conclusion: These results suggest that the timing of PAC is essential for binding audiovisual information and underlies the developmental process in adolescents. Abstract : Phase‐amplitude coupling (PAC) timing underlies maturation for audiovisual speech information integration. The timing of PAC was delayed 20–40 ms in adolescents compared to adults. The timing of PAC was a significant predictor of task performance.